2022
DOI: 10.3389/fneur.2022.1049806
|View full text |Cite|
|
Sign up to set email alerts
|

Vestibular dysfunction is an important contributor to the aging of visuospatial ability in older adults–Data from a computerized test system

Abstract: BackgroundA convergence of research supports a key role of the vestibular system in visuospatial ability. However, visuospatial ability may decline with age. This work aims to elucidate the important contribution of vestibular function to visuospatial ability in old adults through a computerized test system.MethodsPatients with a clinical history of recurrent vertigo and at least failed one vestibular test were included in this cross-sectional study. Healthy controls of three age groups: older, middle-aged, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…The different cognitive processes and domains that might be affected by vestibular lesions are summarized in the widely cited review by Bigelow and Agrawal . During the past few years, this study was endorsed by more recent findings . The most compelling and strongest evidence shows an association between vestibular function and visuospatial cognition, including visuospatial memory, visuospatial navigation, and mental rotation.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…The different cognitive processes and domains that might be affected by vestibular lesions are summarized in the widely cited review by Bigelow and Agrawal . During the past few years, this study was endorsed by more recent findings . The most compelling and strongest evidence shows an association between vestibular function and visuospatial cognition, including visuospatial memory, visuospatial navigation, and mental rotation.…”
Section: Introductionmentioning
confidence: 76%
“…1 During the past few years, this study was endorsed by more recent findings. 2,[4][5][6][7][8][9][10][11] The most compelling and strongest evidence shows an association between vestibular function and visuospatial cognition, including visuospatial memory, visuospatial navigation, and mental rotation. Dysfunctions in all 3 subdomains were identified in persons with vestibular dysfunction and were associated with decreased hippocampal volume.…”
mentioning
confidence: 99%
“…With respect to the latter, the studies by Coughlin et al [40 ▪▪ ] and Lim et al [41 ▪▪ ] seem particularly interesting, especially since the latter was based on a very large sample size. One important development in the area is that more studies are controlling for potential confounds by hearing loss (e.g., [33 ▪▪ ,36 ▪ ,37 ▪▪ ]; see [34] for a review). The last years have also seen the initiation of some large, prospective longitudinal studies [37 ▪▪ ,38].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [36 ▪ ] compared visuospatial function in patients over 60 who had suffered from recurrent vertigo with that in 3 different control groups: young controls, middle-aged controls and older controls. Subjects were excluded if they suffered from hearing loss that affected daily communication, again stressing the importance of controlling for hearing loss.…”
Section: More Evidence For Cognitive Impairment With Vestibular Lossmentioning
confidence: 99%
“…Increasing evidence shows that a decline in vestibular function is related to poor spatial cognitive ability in healthy older adults ( Bigelow et al, 2015 ). Zhang et al (2022) found that (i) visuospatial ability may decline with age, (ii) older adults have weaker visuospatial cognition than younger adults, and (iii) older patients with vestibular dysfunction have worse visuospatial cognition than normal older adults.…”
Section: Introductionmentioning
confidence: 98%